2020
DOI: 10.1503/cmaj.200869
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia and dysgeusia associated with SARS-CoV-2 infection: an age-matched case–control study

Abstract: In the current coronavirus disease 2019 (COVID-19) pandemic, anosmia and dysgeusia have been described as potential symptoms of the disease. On Mar. 21, 2020, a press release from ENT UK (a professional membership body representing ear, nose and throat surgeons in the United Kingdom) and the British Rhinological Society reported anosmia as a symptom in up to 40% of patients in China, South Korea, Germany and Italy. 1 Surprisingly, anosmia and dysgeusia were not reported in the first study describing the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
2
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 22 publications
9
83
2
7
Order By: Relevance
“…The authors concluded that dysgeusia is frequently reported in patients consulting from COVID-19. Other authors also showed similar results [96][97][98][99]. It is still unknown the mechanism by which gustatory dysfunction takes place, but according to Printza et al (2020), SARS-CoV-2 may enter into tongue taste cells via the ACE-2 receptor, which not only is present in pulmonary tissue but also in taste organs (at least in mice) [100].…”
Section: Protein-energy Malnutritionmentioning
confidence: 77%
“…The authors concluded that dysgeusia is frequently reported in patients consulting from COVID-19. Other authors also showed similar results [96][97][98][99]. It is still unknown the mechanism by which gustatory dysfunction takes place, but according to Printza et al (2020), SARS-CoV-2 may enter into tongue taste cells via the ACE-2 receptor, which not only is present in pulmonary tissue but also in taste organs (at least in mice) [100].…”
Section: Protein-energy Malnutritionmentioning
confidence: 77%
“…A total of 11074 COVID-19 patients (mean age 46.7±10.4 years and males 46.9%) were included in the final analysis ( table 1 ). 2 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 The overall prevalence of “loss of smell” in COVID-19 patients was 52.0% (CI: 42.5%-61.6%, I 2 =99.4%) ( Figure 2 ). A total of 21 studies compared these symptoms in COVID-19 patients (n=2196) and controls (n=3425).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 studies compared these symptoms in COVID-19 patients (n=2196) and controls (n=3425). 13 , 14 , 18 , 19 , 21 , 25 , 27 , 28 , 34 , 35 , 36 , 37 , 39 , 40 , 45 , 47 , 48 , 49 , 59 , 60 , 62 “Loss of smell” was associated significantly more in the COVID-19 group compared to non-COVID-19 group (OR: 14.7, CI: 8.9–24.3, p<0.001, I 2 =83.2%) ( Figure 3 ). Among COVID-19 patients, the odds of patients with severe disease and “loss of smell” were significantly low when compared to patients with severe disease and without “loss of smell” (OR: 0.36, CI 0.27–0.48, p <0.01, I 2 =27.4% ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Olfactory ability was assessed by: using validated questionnaires focused on smell dysfunction, in three studies; obtaining objective information on smell impairment through standardised chemosensitive tests with odorants, in five studies; and considering both methods, in five studies (Table 3). 18,20,[24][25][26]29,32,34,37,[40][41][42][43][47][48][49][50][51][52][53][54][55][56][57][58][59] The remaining studies assessed olfactory ability through anamnestic data collection, simple surveys and/or structured, non-validated questionnaires (Table 4). 2,16,17,19,[21][22][23]27,28,30,31,33,35,36,38,39,[44][45][46]…”
Section: Resultsmentioning
confidence: 99%